Role of Smart Homes and Smart Communities in Flexibility Provision - Khajeh, Hosna; Zheng, Ran; Firoozi, Hooman; Laaksonen, Hannu; Shafie-Khah, Miadreza (CRC Press, Taylor & Francis Group, 2021)
Distribution-network-located flexible energy resources such as smart homes and energy communities are potential resources that can contribute to enhancing the flexibility of power systems. In this regard, this chapter first discusses the available demand-side management methods and demand response programs used to incentivize demand-side resources. Then, the role of smart homes and communities in the provision of system-wide and local flexibilities is analyzed. In this way, smart homes and communities are proposed to reshape their consumption and production through their flexible energy resources, including battery energy storage systems, electric vehicles, or their controllable appliances. If they provide local flexibilities, they help the distribution system operator to control voltages and manage congestion of the distribution network. If they provide system-wide flexibilities, they assist the transmission system operator with regulating the frequency of the whole system. Finally, the flexible capacities of a small residential community are estimated as a case study.
Keywords: flexibility services; demand-side flexibility; flexibility provision; smart home energy management; smart energy communities; distribution networks; fi=Sähkötekniikka|en=Electrical Engineering|